THE INFLUENCE OF DEMOGRAPHIC, FINANCIAL LITERACY AND INFORMATION FACTORS ON INVESTMENT DECISION AMONG MILLENIAL GENERATIONS IN BANDUNG - Fitria, Yustitia
Financial literacy is very important for someone in making decisions, especially those relating to daily activities such as in making decisions to save or invest to achieve a predetermined goal. Financial literacy is not only beneficial for the individual but also for the sustainability of a country's economic system. Having good financial literacy will reduce the number of victims in the name of investment. In 2018 the Indonesian stock exchange stated that in 2018 the increase in the number of registered investors increased by 31.97% and an increase in the average number of active investors in trade compared to the end of 2017. According to a survey conducted by The Indonesia Capital Market Institute (TICMI) in millennial, indicating that most millennial have carried out financial management. And from a total of 168 respondents, 61.76% had implemented financial management. Of the various types of financial management activities by investing in the capital market chosen by millennial, there are 54.41%. The author has a strong belief that demographic factors and many other factors vary to define investment management decisions. To conduct this research by collecting primary data by distributing questionnaires and secondary data from relevant journals, textbooks, and research publications. Data will be analyzed using descriptive statistics with the classic assumption test method using 5 types of tests. From the results of this research the authors aim to find out how much the factors above influence the decision to invest among millennial generations in Bandung.